2010
DOI: 10.1142/s1793744210000235
|View full text |Cite
|
Sign up to set email alerts
|

Metabelian Groups With Quadratic Dehn Function and Baumslag–solitar Groups

Abstract: We prove that metabelian locally compact groups in a certain class have quadratic Dehn function. As an application, we embed the solvable Baumslag-Solitar groups in finitely presented metabelian groups with quadratic Dehn function. Also, we prove that Baumslag's finitely presented metabelian groups, in which the lamplighter groups embed, have quadratic Dehn function.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…A polynomial bound on the Dehn functions of m in an earlier version of this article spurred de Cornulier and Tessera to prove in [12] that the Dehn function of p is quadratic for all prime p. They view p , for p prime, as a cocompact lattice in Sol 5 (F p ((t))), which they prove enjoys a quadratic isoperimetric function by adapting Gromov's proof from [18] of the corresponding result for Sol 5 (R). They argue that their methods can be elaborated to cover m for all m.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…A polynomial bound on the Dehn functions of m in an earlier version of this article spurred de Cornulier and Tessera to prove in [12] that the Dehn function of p is quadratic for all prime p. They view p , for p prime, as a cocompact lattice in Sol 5 (F p ((t))), which they prove enjoys a quadratic isoperimetric function by adapting Gromov's proof from [18] of the corresponding result for Sol 5 (R). They argue that their methods can be elaborated to cover m for all m.…”
mentioning
confidence: 89%
“…These groups appear in other guises: both and m are groups of affine matrices and have Cayley graphs that are horocyclic products of trees [3]; for p prime, p is a cocompact lattice in Sol 5 (F p ((t))) [12].…”
mentioning
confidence: 99%
“…Dehn functions (some of these groups contain the Baumslag-Solitar group BS(1, 2)) [59]. (3) The Heisenberg groups of rank ≥ 5, sufficiently large central power of any (infinite) finitely generated nilpotent group of class 2, some finitely generated nilpotent groups of arbitrary nilpotency class [3,185,237,238].…”
Section: ) Cornulier-tessera Examples Of Non-polycyclic Metabelian Gmentioning
confidence: 99%
“…Of course as we have seen (Example 2.22), the Baumslag-Solitar group has exponential Dehn function. But Druţu [73], and later Cornulier and Tessera [59] have shown that metabelian groups of higher ranks can have quadratic Dehn functions. The key property of Young's solvable subgroups is the freedom of choosing them.…”
Section: 1b Nilpotent Groups From Partmentioning
confidence: 99%
See 1 more Smart Citation